Burnout Symptoms among Millennial Teachers in India: The Efficacy of the Emotional Self-Care Online Intervention Program (ESCOIP) - Thomas, Joby; Reyes, Marc Eric S. (Makara Human Behavior Studies in Asia, 2024)
The experiences of millennial teachers—currently comprising the majority of the teaching workforce—have gained attention in scholarly research. The phenomenon of teacher burnout, in particular, has gained greater attention in recent years due to its grave impact on the educational system and the well-being of teachers. Thus, developing an effective online intervention program is crucial to alleviate and avoid burnout among millennial teachers. Using Conklin’s program development model, which involves three phases, (1) planning, (2) design and implementation, and (3) evaluation and program validation, this study investigated the effectiveness of the Emotional Self-Care Online Intervention Program (ESCOIP) in treating burnout symptoms among Indian millennial teachers. The participants comprised teachers from Kerala, South India, born between the early 1980s and mid-1990s (N = 521), who were randomly assigned to the experimental (n = 20) and control (n = 20) groups. We used the sociodemographic survey, the Maslach Burnout Inventory-Educator survey, and focus group discussions to understand the prevalence and complexities involved in this problem. Paired t-test and MANOVA were used for data analysis, while partial eta squared (η2p) measured the extent of the effect of the ESCOIP. Results of the paired t-test and MANOVA revealed a statistically significant effect. Therefore, the program’s outcomes demonstrated that the ESCOIP serves as an effective treatment for the burnout symptoms experienced by millennial teachers.